2010
DOI: 10.1111/j.1468-1331.2009.02816.x
|View full text |Cite
|
Sign up to set email alerts
|

Memantine versus donepezil in mild to moderate Alzheimer’s disease: a randomized trial with magnetic resonance spectroscopy

Abstract: Donepezil and memantine have similar modest clinical and spectroscopic effect on mild to moderate AD. MRS could be useful to monitor progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 42 publications
0
40
1
Order By: Relevance
“…Four of these were longitudinal donepezil treatment studies that found the following: NAA/Cr increased in the dorsolateral prefrontal cortex [33] and bilateral posterior cingulate [36]; NAA/Cr decreased in the left prefrontal region [36] and right hippocampus [32]; a correlation between the change in NAA and the change in ADAS-cog in the parietal lobe [34], and increased mI/Cr in the left occipital lobe and right prefrontal region [36] and decreased mI/Cr in the right hippocampus [32]. A fifth donepezil study found increased NAA in the periventricular white matter and subcortical gray matter in subjects with AD compared to controls [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of these were longitudinal donepezil treatment studies that found the following: NAA/Cr increased in the dorsolateral prefrontal cortex [33] and bilateral posterior cingulate [36]; NAA/Cr decreased in the left prefrontal region [36] and right hippocampus [32]; a correlation between the change in NAA and the change in ADAS-cog in the parietal lobe [34], and increased mI/Cr in the left occipital lobe and right prefrontal region [36] and decreased mI/Cr in the right hippocampus [32]. A fifth donepezil study found increased NAA in the periventricular white matter and subcortical gray matter in subjects with AD compared to controls [35].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the posterior cingulate is a site of known pathology including neuronal loss [50,51] and β-amyloid accumulation [52]. Furthermore, numerous imaging modalities have reported changes in the posterior cingulate in AD patients, including MRS [36,46,53,54,55], PET [52], and functional MRI [56]. Finally, the location of the posterior cingulate within the brain makes it amenable to the acquisition of high-quality 1 H MRS data [57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized trial comparing donepezil with Memantine for 6 months showed no significant differences in clinical scales and metabolite levels. However in the whole sample of 63 patients the changes in the ADAS-cog correlated with the changes in the posteromedial parietal cortex [46] . In a small double blind placebo controlled trial with Memantine the lack of changes in metabolite ratios correlated with the lack of clinical effect in AD compared with controls [47] .…”
Section: Mrs To Track Progression Of Admentioning
confidence: 99%
“…In two of these trials it could be also concluded that the sample size required in a trial of AD patients to see relevant MRS changes was lower than the sample required if it is only based on the equivalent changes in clinical scales such as ADAS-cog [43,46] . A longitudinal study including 42 AD patients and 22 controls that underwent six Magnetic Resonance Spectroscopy studies within an elapse of time of 2 years showed that there is a progressive decline in the NAA/Cr ratios regardless of treatment with cholinesterase inhibitors [48] .…”
Section: Mrs To Track Progression Of Admentioning
confidence: 99%